Diversity of endosymbionts in camellia spiny whitefly, Aleurocanthus camelliae (Hemiptera: Aleyrodidae), estimated by 16S rRNA analysis and their biological implications - Tan, Yanni; Gong, Bing; Zhang, Qiuqiu; Li, Changkun; Weng, Junyi; Zhou, Xia; Jin, Linhong (Frontiers in Microbiology, 2023)
Camellia spiny whitefly, Aleurocanthus camelliae (Hemiptera: Aleyrodidae) is a major pest in tea, which poses a serious threat to tea production. As like in many insects, various symbiotic intergrowth inside A. camelliae may participate in the reproduction, metabolism, and detoxification of the host. However, few reports included research on the microbial composition and influence on A. camelliae growth. We first applied high-throughput sequencing of the V4 region in the 16S rRNA of symbiotic bacteria to study its component and effect on the biological trait of A. camelliae by comparing it with the antibiotic treatment group. The population parameters, survival rate, and fecundity rate of A. camelliae were also analyzed by using the age-stage two-sex life table. Our results demonstrated that phylum Proteobacteria (higher than 96.15%) dominated the whole life cycle of A. camelliae. It unveiled the presence of Candidatus Portiera (primary endosymbiont) (67.15-73.33%), Arsenophonus (5.58-22.89%), Wolbachia (4.53-11.58%), Rickettsia (0.75-2.59%) and Pseudomonas (0.99-1.88%) genus. Antibiotic treatment caused a significant decrease in the endosymbiont which negatively affected the host's biological properties and life process. For example, 1.5% rifampicin treatment caused a longer pre-adult stage in the offspring generation (55.92d) compared to controls (49.75d), and a lower survival rate (0.36) than control (0.60). The decreased intrinsic rate of increase (r) and net reproductive rate (R0), and prolonged mean generation time (T) were signs of all disadvantageous effects associated with symbiotic reduction. Our results first revealed the microbiota status and influence on host A. camelliae and provided important information for understanding the development and management of these important pests in the future.